2021
DOI: 10.1111/crj.13297
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of manual bronchial branch reading technique in navigating conventional rEBUS bronchoscopy in the evaluation of peripheral pulmonary lesion

Abstract: Background Although radial endobronchial ultrasound (rEBUS) is an important verification tool in guided bronchoscopy, a navigational route was not provided. Manual airway mapping allows the bronchoscopist to translate the bronchial branching in computed tomography (CT) into a comparable bronchoscopic road map. We aimed to explore the feasibility of this technique in navigating conventional rEBUS bronchoscopy in the localisation of peripheral pulmonary lesion by determining navigation success and diagnostic yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…The manual navigating method, which has not been widely applied, is not only economical, but also brings a high navigation success rate and an increase diagnostic yield in peripheral pulmonary lesions. [10,11] In the case of the deformation and stenosis of the airways due to the significant granulation tissue in our case, we might not find out the lesion successfully without keeping the bronchial map at hand. To the best of our knowledge, its utility in removal of foreign bodies has not been reported.…”
Section: Discussionmentioning
confidence: 84%
“…The manual navigating method, which has not been widely applied, is not only economical, but also brings a high navigation success rate and an increase diagnostic yield in peripheral pulmonary lesions. [10,11] In the case of the deformation and stenosis of the airways due to the significant granulation tissue in our case, we might not find out the lesion successfully without keeping the bronchial map at hand. To the best of our knowledge, its utility in removal of foreign bodies has not been reported.…”
Section: Discussionmentioning
confidence: 84%
“…The univariate analysis in our study indicated that solid lesions, the presence of bronchus sign, and “within” in r‐EBUS image were associated with higher diagnostic yields, and PPLs located greater than or equal to fifth airway generation were negatively related to clinical yields. Kho et al 9 also determined the factors affecting the diagnostic yield of MN‐guided r‐EBUS and reported a significant higher yield in lesions located less than fifth airway generation. Similarly, the presence of bronchus sign and “within” in r‐EBUS image were reported to be positively related to the yields according a recent large meta‐analysis 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Manual navigation (MN), drawing a schematic representation of the bronchial branching to reach the PPLs simply by looking at the consecutive CT, requires only paper and pencil 7 . This method is not only economical but also brings a high navigation success rate and an increase diagnostic yield in PPLs 8–10 . Unfortunately, scant data about this method have been documented till now.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, manual bronchial branch mapping techniques are emerging, which do not rely on the advanced navigational tools like VBN, and have been applied to EBUS-guided bronchoscopy. Kho et al 100 performed manual bronchial branch mapping of preoperative CT via the bronchial branch reading technology of DICOM software and then identified target lesions by EBUS according to the pre-planned airway road map, resulting in 98.9% successful rate. Our group created a hierarchical clock-scale hand-drawn mapping (HBN) for bronchoscopic navigation.…”
Section: Virtual Bronchoscopy Navigationmentioning
confidence: 99%